SAR Simulation of Human Head Tissues Exposed to Mobile Radio Waves Using FDTD Method - Al Shadidi, Zina A.; Al Shaddadi, Mirfat (Iraqi Journal of Science, 2025)
Increasing the exposure time of radio wave radiation to human tissues is an important factor affecting the SAR (the specific absorption rate) values. This leads to the question of whether overlapping or interfering with electromagnetic waves has a negative impact on our health. Specific absorption rates (SAR) were calculated for the multilayered model of a human head model through different exposure times (30 min, 45 min, 1 hour, 1.5 hours, and 2 hours) at radio wave frequencies of 0.9 GHz and 1.8 GHz emitted from the mobile phones with planer inverted-F antenna (PIFA) and planar monopole antenna. The electromagnetic wave equation was solved using the Finite-Difference Time-Domain Method (FDTD). Different physical phenomena (penetration and interference) were considered for the flow of radio waves penetrating the tissues. Increasing the exposure time of RF waves increased the SAR values in the human head model tissues. The results showed that the cerebrospinal fluid (CSF) was the most affected. The interference effect is very clear. Some values exceeded the safety boundaries set by the Federal Communications Commission (FCC), indicating the close relationship between long-term exposure and the probability of biological damage due to increasing SAR values in tissues. The long exposure period contributes to the interference between the pulses emitted from the antenna.